ANALYSIS OF INDICATOR OF RURAL DEVELOPMENT INDEX (CASE STUDY VILLAGE IN MAGELANG REGENCY 2014-2018) - Dwi Nisaul Husna; Izza Mafruhah; Mohsina Hayat (Journal of Applied Economics in Developing Countries, 2022)
One of the target found in RPJMN 2015 – 2019 is to decrease the amount of backward village up to 5.000 and increase the amount of independent village up to 2.000. Therefore BPS and BAPPENAS issued a measuring instrument called Rural Development Index (RDI) that describes the level of progress or development of the village at a time (BPS, 2018). Magelang Regency is one of 4 regencies in Central Java which become a pilot innovation village in national level. The aims of this research are (1) to find out the description of RDI and (2) to find out the factors that influence the up and down of RDI. This research uses RDI measurement method issued by BPS and BAPPENAS in 2014. This method uses 42 indicators divided into 5 dimensions: (1) basic services; (2) infrastructure conditions; (3) accessibility/ transportation; (4) public services; and (5) governmental administration. The result shows that the RDI score in Magelang Regency in 2014 – 2018 increased even just 0,05. In 2014, RDI is at 64,24 and increased to 64,29 in 2018. Rural development is expected to empowering the community when the Rural Goverment making the development policy so it can be accordance with what the community needs.